2014
DOI: 10.1111/evo.12426
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Past and Present Connectivity Across the Range of a North American Leaf Beetle: Combining Ecological Niche Modeling and a Geographically Explicit Model of Coalescence

Abstract: The leaf beetle Chrysomela aeneicollis occurs across Western North America, either at high elevation or in small, isolated populations along the coast, and thus has a highly fragmented distribution. DNA sequence data (three loci) were collected from five regions across the species range. Population connectivity was examined using traditional ecological niche modeling, which suggested that gene flow could occur among regions now and in the past. We developed geographically explicit coalescence models of sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…A similar observation has been observed in Dellicour et al . (), highlighting the limitations of the ENM approach for estimating current and past species ranges. From a practical point of view, a main issue in ENM based range estimates is the availability of past environmental data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar observation has been observed in Dellicour et al . (), highlighting the limitations of the ENM approach for estimating current and past species ranges. From a practical point of view, a main issue in ENM based range estimates is the availability of past environmental data.…”
Section: Discussionmentioning
confidence: 99%
“…In bumblebees, it has been suggested that determining habitat suitability, which is analogous to the ENM approach, can be used as a baseline approach for understanding species-specific responses to climate change (Herrera et al, 2014;Lecocq et al, 2015a;Rasmont et al, 2015). Coalescence-based genetic models have been combined with ENM in numerous studies (Carstens & Richards, 2007;Shepard & Burbrink, 2008Solomon et al, 2008;Bagley et al, 2013;Dellicour et al, 2014a). More recently, there have been studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is hard to find cryptic refugia as well as microhabitats differences between codistributed species (Dellicour et al. , ). Although habitats of the two Eleutherococcus species overlap at a regional scale, the small‐scale niche differences (e.g., altitude) are ignored by the current simulations due to the low resolution of ancient climate data.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is indeed often observed in insects (e.g. Dellicour et al ., ; Quinzin & Mardulyn, ) and other animals (Zink & Barrowclough, ; Peters, Bolender & Pearce, ), probably due to the smaller effective population size associated with the mitochondrial genome (stronger genetic drift) and to a history of recurrent adaptive selection (Bazin, GlĂ©min & Galtier, ).…”
Section: Discussionmentioning
confidence: 99%